Bodies in Contempt: Gender, Class and Disability Intersections in Workplace Discrimination Claims - Dick-Mosher, Jenny (Disability Studies Quarterly, 2015)
This article draws on theories of gendered organizations to examine discrimination against people with disabilities in the workplace. A sample of 200 cases that document disability discrimination lawsuits was drawn from the Westlaw legal database. Each case was coded for gender, job, disability and discrimination type and analyzed using multinomial logistic models. Of those 200 cases, 34 were selected for in depth qualitative analysis. This study finds that disability type, job type, and gender do have an influence on the type of discrimination someone is likely to experience. In addition, the qualitative analysis finds that the social processes of discrimination differ based on job type and gender pointing to intersections of disability and class as well as gender and disability.